(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2007)
The great similar tooth morphologies that characterized the sharks of the genus Carcharhinus have suggested that the Neogene Mediterranean Sea were inhabited by only one or two widespread carcharhinid taxa, Carcharhinus egertoni and C. priscus. The first Mediterranean Pliocene record of five new shark species included into Carcharhinus, C. aff. brachyurus, C. falciformis, C. leucas, C. perezi, and C. plumbeus, have been identified by the review of some shark teeth from Tuscany (Italy) and housed in the Italian Museums of the Universities of Firenze, Bologna, and Pisa. Moreover, the Mediterranean records of the two Recent C. longimanus and C. obscurus has been confirmed too. Paleobiogeographic and palaeoecologic analysis have been produced on the presence of some species absent or doubtful for the extant Mediterranean shark community.